Qualidade de vida visual em portadores de esclerose múltipla com e sem história de neurite óptica desmielinizante. - Luciano Mesquita Simao (2009)
INTRODUCTION: Multiple Sclerosis (MS) is an immune-mediated inflammatory disease of the central nervous system that affects the visual system either as an optic neuritis or as a relentless subclinical disease. Patients with MS frequently complain of blurred vision or imprecise visual discomfort without any abnormality in visual acuity test. Presumably these symptoms may impair patients ability to perform their daily activities and the vision-related quality of life may be compromised. OBJECTIVE: Toinvestigate the vision-related quality of life in MS patients with correlation to previous episode of demyelinating optic neuritis. PARTICIPANTS AND METHODS: A crosssectional study in a sample of 69 MS patients and 62 healthy controls was conducted. We applied the Brazilian version of the 25-Item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) and the following visual function tests: Snellen visual acuity (VA), Farnsworth-Munsell 100-hue color vision (FM-100hue), Low-ContrastSloan Letters Charts (LCSLC) and Humphrey visual field (HVF). The expanded disability status scale (EDSS) was also recorded. Comparative analyses using the following tests: chi-square, Student t, ANOVA, Mann Whitney U and Kruskal-Wallis were performed between the MS cohort and controls for comparison of the visual questionnaire scales, visual function tests, clinical and demographic features. Spearman rank correlation was used in MS cohort and controls between NEI VFQ-25scores and the visual function tests. RESULTS: A statistical significant comparison between the MS cohort and controls was observed in the composite score and five subscales of the visual questionnaire. The same statistical significant results were obtained with the comparison of all visual function tests between the MS cohort and controls, except for visual acuity and Sloan chart 100% contrast tests. However, thecomparison of the questionnaire among the subgroups of MS patients with and without previous episode of demyelinating optic neuritis and controls was poorly correlated. The composite score of the NEI VFQ-25 in the MS cohort correlated well to vision function tests including VA (r = -0.25, P=0.04), LCSLC 100% (r = 0.28; P=0.02), LCSLC 5% (r = 0.40; P<0.01), LCSLC 1.25% (r = 0.35; P<0.01), LCSLC 0.6% (r = 0.31; P=0.01), HVF (r = 0.34, P<0.01) and EDSS (r = -0.32, P=0.01). The FM-100hue test did not show statistically significant correlation to the compositescore (r = -0.31; P=0.70). In the control group, the composite score of the NEI VFQ- 25 correlated well to only one vision function test as LCSLC 1.25% (r = 0.41; P<0.01). CONCLUSION: Multiple sclerosis patients had worse scores in all tests regarding to the vision-related quality of life study in comparison to controls. Abnormalities of visual function tests may explain the subjective visual complaints. Previous episode ofoptic neuritis did not suggest a poorer vision-related quality of life in the study cohort.